2022
DOI: 10.34172/bi.2022.24253
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes as versatile nanoscaled biocompartments in cancer therapy and/or resistance

Abstract: Cancer remains to be a major hurdle to global health. Exosomes as a versatile bio-derived platform, hold a bright prospect in nano-scaled delivery/targeting strategies. Shreds of evidence indicate that exosomes have a critical role in drug resistance in cancer cells through various mechanisms including shuttling of miRNAs, drug efflux transporters, and anti-apoptotic signaling. Exosomes’ cargo, particularly miRNAs, may exert both resistance and in a few cases sensitivity to the anticancer agents in targeted ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…the contents of patient's exosomes significantly change. [12][13][14][15] The tumor affects the content (cargo) of proteins and oligonucleotides in the serum exosomes. Moreover, the blood serum of oncologic patients has been used as a source of exosomes with upregulation of several miRNAs.…”
Section: Cell Cultures and Obtaining The Drug-resistant Sublinementioning
confidence: 99%
See 1 more Smart Citation
“…the contents of patient's exosomes significantly change. [12][13][14][15] The tumor affects the content (cargo) of proteins and oligonucleotides in the serum exosomes. Moreover, the blood serum of oncologic patients has been used as a source of exosomes with upregulation of several miRNAs.…”
Section: Cell Cultures and Obtaining The Drug-resistant Sublinementioning
confidence: 99%
“…For instance, the considerable upregulation of miR-10a-5p, miR-19b-3p, miR-215-5p, and miR-18a-5p in exosomes of gastric cancer patients in comparison with healthy control samples was revealed by Houman Kahroba et al 13 Recent studies of exosomes have shown that the development of multidrug resistance (MDR) in tumor cells occurs, among other things, with the participation of exosomes, which, due to their nature, can ensure the spread of resistance throughout the pool of tumor cells. 12 Thus, in experiments on in vitro cultured breast cancer cells, microvesicles isolated from resistant cells contained an increased amount of P-glycoprotein, one of the main ABC transporters, and the cultivation of sensitive cells with such exosomes leads to the accumulation of exogenous P-glycoprotein in cells and a significant increase in drug resistance. 16,17 Further development of these studies has enabled the substantial increase in the amount of groups of biologically active molecules, which are transferred by the microvesicles of resistant cells and are able to trigger drug resistance in receiving cells.…”
Section: Cell Cultures and Obtaining The Drug-resistant Sublinementioning
confidence: 99%
“…8 As a kind of paracrine product, exosomes are nanoscale extracellular vesicles secreted from the cell membrane which contain mRNA, miRNA, cytoplasmic and membrane proteins from the mother cells. 9,10 MSC-derived exosomes (MSC-exo) have similar immunomodulatory effects to MSCs and can modulate innate and adaptive immune responses by inhibiting the T lymphocyte function, decreasing the activation and proliferation of B cells, affecting macrophage differentiation and dendritic cell maturation, and inhibiting the cytotoxic activity of natural killer cells. 11,12 Meanwhile, exosomes can repair injury by inhibiting cell fibrosis and apoptosis and promoting cell proliferation, migration, differentiation and angiogenesis through regulating Wnt, NF-κB, TGF-β1/Smad and other signaling pathways.…”
Section: Introductionmentioning
confidence: 99%